A suite of neurophotonic tools to underpin the contribution of internal brain states in fMRI. (June 2021) - Mächler, Philipp; Broggini, Thomas; Mateo, Celine; Thunemann, Martin; Fomin-Thunemann, Natalie; Doran, Patrick R.; Sencan, Ikbal; Kilic, Kivilcim; Desjardins, Michèle; Uhlirova, Hana; Yaseen, Mohammad A.; Boas, David A.; et al.
Abstract: Recent developments in optical microscopy, applicable for large-scale and longitudinal imaging of cortical activity in behaving animals, open unprecedented opportunities to gain a deeper understanding of neurovascular and neurometabolic coupling during different brain states. Future studies will leverage these tools to deliver foundational knowledge about brain state-dependent regulation of cerebral blood flow and metabolism, as well as regulation as a function of brain maturation and aging. This knowledge is of critical importance to interpret hemodynamic signals observed with functional magnetic resonance imaging (fMRI). Highlights: Optical probes for neuromodulation may allow direct measurements of cortical states. Relative contribution of oxidative and glycolytic metabolism to hemodynamics may be state-dependent. Loss of aerobic glycolysis in aging may be related to weakening of neuromodulation. Neuromodulation can alter vasomotion oscillations, a measure of brain state observed through fMRI.